Design of CMOS-MEMS based thermoelectric generator - Rahman, Z.H.A. (2013)
This paper presents the design of micro-scale thermoelectric generator (TEG) using CMOS-MEMS technology. Electrical energy is obtained by means of thermal energy harvesting technique. Thermal energy harvesting has become a promising solution to power up low power system such as wireless sensor networks (WSNs) and portable devices. Thermal energy or heat which is widely available in natural and also human made environments can be converted into electrical power using Seebeck effect. The proposed TEG is compatible with standard CMOS technology which consists of p-doped and n-doped polysilicon thermocouples arranged electrically in series and thermally in parallel. In order to increase the temperature difference between the hot and cold parts, a layer of heat sink with low thermal conductivity material is insulated at the cold part area. Trenches are included in-between each thermocouple to disperse heat efficiently to ambient air. Post-CMOS process is included to illustrate proper procedures for a successful device release. Simulation results show that with temperature difference of 10 K, output voltage and power attained is 301 mV and 45 Î¼W, respectively. Â© 2013 IEEE.